Application of Multisensory in Learning Alphabets Identification Skills for Special Education Students - Noor Syamilah Bt Md Maliki; Mohd Hanafi Mohd Yasin (Department of Special Education, 2017)
Multisensory is a method of learning and teaching which integrates all sensories. The objective of this study is to determine the level of progress in learning alphabets identification skills after the application of the multisensory method in special education learning for children with learning disabilities. This study is conducted using a quasi-experimental approach upon six students with learning disabilities who are selected by way of purposive sampling. The students are divided into two groups. Group A is the treatment group while Group B is the control group. The students in Group A receive learning intervention through multisensory while the students in Group B receive learning through traditional teaching methods. Both teaching methods are carried out for a period of four weeks. The research instruments consist of pre-test and post-test adapted from Clay (2005) Observation Survey of Early Literacy Achievement. The results are analyzed descriptively by way of mean and percentages. The research results show improvement of the test scores of the treatment group as compared to the control group. This indicates that the multisensory method is effective and appropriate to be applied in relation to children with special needs due to their learning disabilities in terms of alphabets identification.